Highways, byways, and road systems in the pre-modern world - Alcock, Susan E.; Bodel, John P. 1957-.; Talbert, Richard J. A. 1947-. (Chichester, West Sussex Wiley-Blackwell, 2012)
"The unparalleled network of roads in the empire of ancient Rome was a remarkable achievement--yet this Roman road network is just the most notable example of an important feature of many pre-modern societies worldwide. Highways, Byways, and Road Systems in the Pre-Modern World presents a comparative analysis of several sophisticated systems of overland transport and communication networks across pre-modern cultures. Featuring contributions from an international team of scholars, these readings delve deeply into the societal, cultural, and religious implications of various transportation networks around the globe. The latest research from the Mediterranean and the Near East is brought together with fresh work from the Americas, Africa, and Asia to reveal the significance and logistics of the movement of people and ideas in the pre-modern world. Highways, Byways, and Road Systems in the Pre-Modern World sheds important new light--and fills a gap in contemporary scholarship--by exploring the importance and interconnectedness of the countless physical pathways of peoples and cultures"--Provided by publisher.
Keywords: Roads -- Social aspects; Roads -- History